Extreme Fabulations Science Fictions of Life - Shaviro, Steven (Goldsmiths Press, 2021)
An examination of science fiction narratives and the light they shed on human life, the unknowable future, and the vagaries of unforeseeable change. With this book, Steven Shaviro offers a thought experiment. He discusses a number of science fiction narratives: three novels, one novella, three short stories, and one musical concept album. Shaviro not only analyzes these works in detail but also uses them to ask questions about human, and more generally, biological life: about its stubborn insistence and yet fragility; about the possibilities and perils of seeking to control it; about the aesthetic and social dimensions of human existence, in relation to the nonhuman; and about the ethical value of human life under conditions of extreme oppression and devastation. Shaviro pursues these questions through the medium of science fiction because this form of storytelling offers us a unique way of grappling with issues that deeply and unavoidably concern us but that are intractable to rational argumentation or to empirical verification. The future is unavoidably vague and multifarious; it stubbornly resists our efforts to know it in advance, let alone to guide it or circumscribe it. But science fiction takes up this very vagueness and indeterminacy and renders it into the form of a self-consciously fictional narrative. It gives us characters who experience, and respond to, the vagaries of unforeseeable change.